Recovery of Borrelia burgdorferi by filtration. - Jobe, D A (1993)
Bacterial contamination frequently interferes with successful recovery of the Lyme spirochete from cultures of tissue from Borrelia burgdorferi-infected humans, rodents, or ticks. We used 0.20- and 0.45-microns-pore-size syringe-tip filters to recover spirochetes from cultures contaminated with other bacteria. Low concentrations (1 to 10/ml) of B. burgdorferi organisms could be recovered from cultures seeded with 1 x 10(8) to 4 x 10(8) Staphylococcus aureus, Streptococcus faecium, Escherichia coli, or Bacillus subtilis organisms per ml. We also used this technique to recover B. burgdorferi from contaminated environmental and clinical cultures of B. burgdorferi. We conclude the filtration is an efficient method for recovering Lyme spirochetes from contaminated samples and increasing the number of successful isolations of B. burgdorferi.